QUALITY CORRELATION PELAYANAN DAN KINERJA APARATUR PEMBAYARAN PAJAK BUMI DAN BANGUNAN KOTA PALU - Ade Irma (Sekolah Tinggi Pariwisata Mataram, 2022)
This research aims at finding out the quality of property tax service ah. Office for Management of Regional Revenue, Finance and Assets, Palu. This is a qualitative research. The informants of this research are the public servants and taxpayers taken purposively, and the techniques of the data collection are observations, interviews, and documentations, while the techniques of data analysis are data reduction, data display, conclusion taking and verification. The result of this research shows that the quality of property tax service at Office for Management of Regional Revenue, Finance and Assets Palu not maximal because the physical display service room is less convenient because it does not match the number of taxpayers so much and parking are irregular, then the accuracy of the time service has not been as expected because of the time service providers sometimes employees are not in place so that the taxpayer made to wait, as well as employees who are less responsive response caused by disorders such taknis electrical problems.